(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined effective communication in electronic environments among students of Ekiti State University, Ado-Ekiti, Nigeria. Anchored on Media Richness Theory and the Technology Acceptance Model, the study sought to assess students’ use of electronic platforms, the challenges encountered, and the factors influencing communication effectiveness. A descriptive survey design was adopted; a sample of 384 undergraduate students were selected through multistage sampling procedure. Data were collected using a validated questionnaire titled, “Electronic Communication Effectiveness Questionnaire” ECEQ, with a reliability coefficient of r = 0.86. Descriptive statistics, t-test, and multiple regression analysis were used to analyze data at 0.05 level of significance. Findings revealed that WhatsApp, Telegram, and Google Classroom were the most frequently used platforms for academic interaction, while email and institutional Learning Management Systems were underutilized. Students perceived electronic communication as effective for information sharing and group collaboration, but ineffective for complex academic discussions due to poor network access, digital distractions, and low digital literacy skills. Regression results showed that digital literacy β = .32, p < .001, stable internet access β = .28, p < .001, and lecturers’ responsiveness β = .21, p < .01 significantly predicted effective communication in electronic environments, accounting for 47% of the variance. Significant differences existed in perceived effectiveness based on level of study. The study concluded that while electronic communication enhances flexibility and access to learning resources among EKSU students, its effectiveness is constrained by infrastructural and skill-related challenges. It recommended that the university management should invest in reliable internet infrastructure, integrate digital literacy training into the General Studies curriculum, and train lecturers on effective online facilitation strategies to optimize electronic communication for academic purposes.